2022
DOI: 10.3390/microorganisms10020330
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of the Microbiota Has a Modest but Important Impact on the Fungal Burden of the Heart and Lungs during Early Systemic Candida auris Infection in Neutropenic Mice

Abstract: The progression and systemic pathobiology of C. auris in the absence of a microbiota have not been described. Here, we describe the influence of the microbiota during the first 5 days of C. auris infection in germ-free or antibiotic-depleted mice. Depletion of the bacterial microbiota in both germ-free and antibiotic-depleted models results in a modest but important increase in the early stages of C. auris infection. Particularly the heart and lungs, followed by the cecum, uterus, and stomach, of intravenously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…A limitation of this study is that the fungal burden was tested in the kidneys, the heart and the brain. Other authors found that intravenous C. auris infection produced high fungal burden in neutropenic mice in the lungs, cecum, uterus and stomach [ 26 ]. However, previous studies have shown that the heart and kidneys are the main targets in cases of invasive infections caused by C. auris , together with the CNS involvement [ 12 , 27 , 28 , 29 ]; the fungal burden in these sites, especially in the heart, is the primary cause for death in mice [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of this study is that the fungal burden was tested in the kidneys, the heart and the brain. Other authors found that intravenous C. auris infection produced high fungal burden in neutropenic mice in the lungs, cecum, uterus and stomach [ 26 ]. However, previous studies have shown that the heart and kidneys are the main targets in cases of invasive infections caused by C. auris , together with the CNS involvement [ 12 , 27 , 28 , 29 ]; the fungal burden in these sites, especially in the heart, is the primary cause for death in mice [ 12 ].…”
Section: Discussionmentioning
confidence: 99%